Descriptive Analysis of Fusion Food Plating Techniques on Opor Ayam as an Attraction of Traditional Culinary - Yudhistira, Arnoldo Aria; Cung, Joshua; Dwi Cahyanto, Bima (Gastronomy and Culinary Art, 2026)
This study aims to describe the application of fusion food plating techniques on opor ayam and to identify informants’ responses to the resulting visual appeal. The study employs a descriptive qualitative approach, with data collected through observation, semi-structured interviews, and documentation. The informants consist of five individuals selected purposively based on their relevance in the culinary field. Data analysis is conducted using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results indicate that fusion plating produces significant visual differentiation compared to conventional plating. The differences are evident in the arrangement of composition, placement of focal points, use of color contrast, and utilization of negative space, all of which create a more modern and structured presentation. All informants perceive fusion plating as more attractive, neat, and capable of conveying a premium impression. In addition, the more organized visual appearance shapes higher expectations of quality, even though the taste composition remains unchanged. However, this visual innovation must still preserve the traditional identity of opor ayam. Therefore, fusion plating techniques can be viewed as an adaptive strategy to enhance the appeal of traditional cuisine without altering its fundamental characteristics.